Multiquantitative control of pesticides in treated sugar beet seeds - Chervyakova, L.; Panchenko, T.; Tsurkan, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To develop a method for the determination of thiamethoxam, bifenthrin, hymexazole and thiram in treated sugar beet seeds in one analysis. Methods. The active substances were analyzed by method of thin-layer chromatography. The linear range of dependence of the area of chromatographic zones on the amount of active substance was estimated by mathematical and statistical method using correlation and regression analysis. Results. The determination of pesticides includes the main stages: characterization of active substances by polarity; their extraction from the analyzed matrix; chromatographic separation, identification and quantification. The dipole moment of a compound (μ, Debye) is an integral indicator in the analysis, characterizing its polarity and physicochemical properties. Accordingly: bifenthrine is a non-polar compound with a dipole moment of 0.38 D; thiram, hymexazole, thiamethoxam are low-polar compounds with a dipole moment of 3.45, 3.99, and 5.55 D, respectively. The extractant that provides the most complete extraction is ethanol (ε 24.3). Separation — in a thin layer of silica gel adsorbent with acidification of the thin layer with a 10% solution of acetic acid in ethanol in the mobile phase of hexane + ethanol (ε = 8.42). The compounds are identified under a chromatoscope (λ 254 nm) and using a silver ammonia reagent with UV irradiation (brown zones of localization of active substances on the light background of the chromatogram). The dependence of the area of the chromatographic zone of a compound (S, mm2) on its amount (C, μg) is linear in the detection range for: thiamethoxam 0.1 — 0.7 μg; thiram 0.1 — 1.0 μg; hymexazole 0.5 — 2.0 μg; bifenthrine 0.3 — 2.0 μg and is described by the corresponding regression equation: S = 8.345 S + 1.3395; S = 40.87 S + 6.4596; S = 8.83 S + 0.125; S = 4.4304 S + 4.8996. Conclusions. The developed methodology allows for the analytical control of thiamethoxam, thiram, hymexazole and bifenthrin in the treated sugar beet seeds in the presence of different combinations and quantities during one analysis with high accuracy, reliability and reproducibility.